Exploring the determinants of COVID-19 mortality rate worldwide / Elya Sara Syuhada Azhar ... [et al.] - Azhar, Elya Sara Syuhada; Che Sulaiman, Nur Salsabila; Rosli, Siti Nuraqina; Mohamed Yusof, Noreha (Universiti Teknologi MARA, Sabah, 2023)
SARS-CoV-2, also known as COVID-19, is a coronavirus that causes severe acute respiratory syndrome. The recent outbreak of COVID-19 had caught the world by surprise, resulting in millions of confirmed infected cases and 5,325,079 deaths documented worldwide. This study aims to explore the significant factors associated with COVID-19 mortality rate by focusing on the number of active cases, total cases, critical cases, vaccination doses, and screening tests. Secondary data from 219 countries was retrieved from CNN Health, Worldometer, and GitHub Our World in Data, which was later analysed using multiple linear regression. The results showed that total cases and vaccination doses of COVID-19 are the significant factors associated with COVID-19 mortality rate; active cases, critical cases, and screening tests were found to have insignificant relationships to COVID-19 mortality rate. This study offers further recommendations which can be accomplished using the updated data that include the patients' common comorbidities, such as obesity, hypertension, and diabetes mellitus.